Resource Use Efficiency and Marginal Productivity of Potato Cultivation in Haryana - Shivam,; Megha Goyal,; Ghalawat, Suman; Joginder Singh Malik,; Kautilya Chaudhary, (Indian Journal of Extension Education, 2025)
The study conducted in 2024 aimed to analyse the efficiency of resource utilisation and the marginal value productivity (MVP) of inputs in potato farming across three prominent districts of Haryana—Sonipat, Karnal, and Kurukshetra. A sample of 120 farmers cultivating potatoes was chosen through convenience sampling. To evaluate the impact of various inputs on yield variation, the Cobb-Douglas production function was applied to estimate the respective regression coefficients. Marginal Value Productivities were derived and compared with Marginal Factor Cost (MFC), taken as unity due to monetary standardisation of variables. The results revealed that seed and manure & and fertilizers were significantly underutilised in all districts, indicating potential for increased productivity through better input management. In contrast, human labour and irrigation were overutilized, often yielding negative MVPs, suggesting inefficiencies in labour deployment and water use. Mechanization, reflected through machine labour, was also found to be underutilized across all districts, indicating the need for greater adoption of efficient farm machinery. The overall coefficients indicated decreasing returns to scale, underscoring the need for balanced and efficient resource allocation. The findings provide actionable insights into optimizing input use to improve farm-level productivity and profitability in potato cultivation in Haryana.